Efeitos cognitivos da escolaridade do SENAI e da escola acadêmica convencional: uma pedagogia para cada classe social? - Frigotto, Gaudêncio (1977)
In the present atudy, facultu and contribution Df different methodo'Logies and styles of pedal'logic aotion in youths social ZOIJ alass are discu8sed. 1t refere ·e-o a case study, having as a sampLe, minoI' age apprentice pupila 0, the Serviço Nacional de Aprendizagem Industrial - SENAI (Na 'tional Serviae of Industrial Apprenticeship), of Rio de Janeiro Citlh as compared lJith primary and secondary academia school pupila. Qualitative data demonstrate that the anatysed p~ dagogic action of the academic 8choo'Ls is .structured üJithin a generic conception, diffused and uneoncern.ed, hel.d to pedagogic idiotism, myths and anti-myths. The same v 'LUBS and language,as weZl as the same social high alass achool Byllabus~ howeverJare maintainedJ without haoing the minimum human and material under structure. SENAI's pedagogic action is restricted to objecti Ves too much specific and pragmatic~ trying to teach what it is thought to be good. It uses a teaching methodology for the sociaL and linguistic universe of the social low class pupiLs. The quantitatioe resuLtsJ partLy unconcLusive J de monstrate that the methodoLogic differenc8S among groups~ although intense~ do not influence in tne cognitiv components, thus causing mensurable cnanges during a year. r oreover, results reveaL, there nas not exiated significant cognitive pl'Ofits bef»3en the 7th and 8th primary grades, and the 8th primary and 1st se- • condary grades. In a general way, in the p'resent studYJ it is manifested a poor influence of the schooL in the social. Low class pupiLa cognitive changes. One of the significant resuLta of the presem study ia reLated to a strong cognitive and unc09'nitive interaction components. The qualitative data give evidence that the organizationaL atmosphere~ rich in 8timuLi~ in a presence of tangibLe and concrete substantive contents~ as weLL as a teaching methodoLogy~ thus alLowing a progre8sive advance~ and make p088ible for the 80cially low claS8 pupils~ the internaLization of auto- -reLiance. School 8ucce88 ar faiLures both seem to mark the pupiLs~ indeLibly. In the present conte:ct~ th.ere appears a non cognitive effect as a resuLt of a much more perceptibLe cogniti tM apprentieeship. The message - methodoLo 'li, eontent8~ambient~ etc. - wiLl be the means.